KAJIAN LITERATUR SISTEMATIS PRAGMATISME JOHN DEWEY DAN KONTRIBUSINYA TERHADAP PENDIDIKAN INDONESIA - Nurul Qomariah; Endang Fauziati (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2023)
John Dewey’s pragmatic thinking is able to contribute to Indonesian education, especially in the curriculum which can provide freedom for students to be free, active, and flexible learning, as well as strengthen their character of attitudes. The purpose of this research is to examine John Dewey’s pragmatic thinking and his contribution to Indonesian Education over the last few decades. The research method used in this systematic review focuses on a narrative summary of thematic analysis which includes three stages: planning the review, conducting the review, and reporting the review. The results showed that current research trends and focus are more absorbed on the processes and outcomes such as developing the basic framework education, quality of learning, quality of education, learning strategies, management of education, development of education systems, development of learning methods. In addition, there are also several strategies that can be developed through John Dewey’s pragmatic thinking, such as logical thinking, metaphysics, theory of knowledge of freedom, opinion, creativity in effective, quality, and modern learning practices. These findings indicate that future study must focus on comprehensive teaching and learning preparation and changing classroom practices which adopting John Dewey’s pragmatist concept of thinking to respond 21st century skills.